Association of Thrombocytopenia in Pregnant Women with COVID-19 Vaccination in the Post-COVID Era - Sultan, Kainat; Khan, Saba; Tariq, Simrah; Maaz, Muhammad; Shahmina; Akhund, Ilqa Ikram (Indus Journal of Bioscience Research, 2025)
Background: Thrombocytopenia is the second most frequent haematological abnormality in pregnancy, up to 10% of pregnant patients, and it often concerns general practitioners. Following the introduction of mass vaccination against COVID-19, fears have been raised about potential association between COVID-19 vaccination and haematological complications, including thrombocytopenia. There is limited information on the safety of COVID-19 vaccines during pregnancy, especially in low- and middle-income countries, despite global vaccination campaigns. Objective: To explore the link between thrombocytopenia in pregnancy and the COVID-19 vaccine in the COVID-19 era. Methodology: This case control study was carried out at the Department of Gynaecology and Obstetrics, JPMC, Karachi for duration of six months. A sample of 189 pregnant women, aged >20 weeks gestation, were recruited based on non-probability consecutive sampling. Subjects were stratified according to vaccination and had thrombocytopenia defined (platelet counts